Distribution modeling of Rafflesia schadenbergiana and Rafflesia consueloea using multi criteria decision analysis-analytical hierarchy process in GIS - Menzuela Hidalgo Ancheta (Journal of Degraded and Mining Lands Management, 2021)
The identification of potential habitats of the largest and smallest flowering parasitic Rafflesia in the Philippines is a prerequisite in conservation of species and preservation of their habitats which have been being degraded due to anthropogenic activities and climate change. This research aimed at revealing the possible habitat suitability for Rafflesia schadenbergiana Göppert ex Hieron and Rafflesia consueloae Galindon, Ong Fernando throughout the Philippines using Geographic Information Systems (GIS). The selection criteria in this research were based on four parameters (elevation, annual rainfall, temperature, and land use / land classification) identified during the extensive literature review. The generated map shows that the optimal growth of the Rafflesia schadenbergiana can be observed with a temperature range of 20–22°C while Rafflesia consueloae can thrive within 24°C to 25°C. The importance of these criteria was evaluated using a pairwise comparison method and the final weight was computed for each criterion. Setting up of the values suiting the subject species was followed by weighted overlay analysis. The final output is the distribution and habitat suitability of the subject species.